ANALISIS YURIDIS SENGKETA TANAH ULAYAT DI LUBUK BASUNG SUMATERA BARAT - Adella Maulana; Surastini Fitriasih (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
West Sumatra has a lot of ulayat lands, namely land that is jointly owned by customary law communities, whether it belongs to a certain suku (tribe) or kaum (people). This often results in land conflits. This study aims to review the protection of land customary rights in Indonesia and analyze how the decision of the Lubuk Basung District Court Number 6/Pdt.G/2021/PN Lbb protects the land customary rights. This study uses a qualitative method with a normative juridical approach. Results of the study stated that the Judge decided that the certificate registration process made without the approval of Kaum and Head of Mamak Waris was considered legally flawed and prohibited under Minangkabau customary law. This study also finds that this dispute occurs because of a confusion about the origin of the object of dispute, a thing that is common because of the characteristics of ulayat land that are inherited generation to generation.